2006
DOI: 10.1016/j.visres.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Age related differences in learning with the useful field of view

Abstract: In naturalistic tasks, subjects often interact with a cluttered visual environment in which they need to divide their attention simultaneously among multiple objects and tasks. Previous work examining the effects of aging in tasks that approximate these real world demands have shown that performance often declines with age. For example, when subjects must perform central and peripheral visual tasks simultaneously in a Useful Field of View (UFOV) task, performance on the peripheral task declines relative to whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 31 publications
6
57
1
Order By: Relevance
“…However, our findings show that both young and older adults can flexibly learn new decision criteria (i.e., categorical boundary) that determine the categorical membership of visual forms on the basis of stimulus-response associations. This is consistent with recent studies showing similar performance across age groups for probabilistic learning of categories on the basis of implicit stimulus-outcome associations (Fera et al, 2005;Davis, Klebe, Bever, & Spring, 1998) and with theoretical and psychophysical evidence that older adults can match the performance of younger adults given sufficient practice (Ratcliff, Thapar, & McKoon, 2006;Richards, Bennett, & Sekuler, 2006). Interestingly, age-related differences in perceptual learning have been reported for speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…However, our findings show that both young and older adults can flexibly learn new decision criteria (i.e., categorical boundary) that determine the categorical membership of visual forms on the basis of stimulus-response associations. This is consistent with recent studies showing similar performance across age groups for probabilistic learning of categories on the basis of implicit stimulus-outcome associations (Fera et al, 2005;Davis, Klebe, Bever, & Spring, 1998) and with theoretical and psychophysical evidence that older adults can match the performance of younger adults given sufficient practice (Ratcliff, Thapar, & McKoon, 2006;Richards, Bennett, & Sekuler, 2006). Interestingly, age-related differences in perceptual learning have been reported for speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…Effective training methods to counter the normal age-related deterioration in spatial selective attentional capacities would be extremely valuable. Playing a driving game could help older adults maintain their existing skills, or perhaps even reverse decline, especially in tasks in which divided attentional costs are involved (Bherer, Kramer, & Peterson, 2008;Cassavaugh & Kramer, 2009;Richards, Bennett, & Sekuler, 2006).…”
Section: Driving-racing Videogamesmentioning
confidence: 99%
“…Andersen et al (2010) found that training with subthreshold stimuli improved older observers when performing a texture discrimination task. Richards et al (2006) found that older observers could improve their performance in divided attention through repeated training with the UFOV task. Similarly, improvements in contrast sensitivity through training were found for older adults in a recent study (Phan and Ni, 2011).…”
Section: Discussionmentioning
confidence: 96%